KEBIJAKAN PENANGANAN KASUS HUMAN TRAFFICKING DI UKRAINA MELALUI PERAN INTERNATIONAL ORGANIZATION FOR MIGRATION - Hendra Maujana Saragih; Syifa Nur Islamiah (Magister Administrasi Publik FISIP Universitas Mulawarman, 2019)
Human trafficking can be divided into three components related to: recruitment of people, ways of controlling people, and the purpose of exploitation. Ukraine is a country of origin and to a certain extent is a transit country for people who declare themselves in situations of slavery. Where in recent years Ukraine has become a destination country for victims of human trafficking, and also the case of human trafficking in the country of Ukraine is also increasingly widespread. IOM's mission in Ukraine is to continue to struggle in the face of the challenges of human trafficking, to assist the Government in improving the migration management system, and to create migrant health programs (inclusive and policy).Keywords: Human Trafficking, Ukraine, International Organization for Migration